2016
DOI: 10.1038/bjc.2016.176
|View full text |Cite
|
Sign up to set email alerts
|

Adverse prognostic impact of the CpG island methylator phenotype in metastatic colorectal cancer

Abstract: Background:The association between the CpG island methylator phenotype (CIMP) and clinical outcomes in metastatic colorectal cancer remains unclear. We investigated the prognostic impact of CIMP in patients with metastatic colorectal cancer treated with systemic chemotherapy.Methods:Eight CIMP-specific promoters (CACNA1G, IGF2, NEUROG1, RUNX3, SOCS1, CDKN2A, CRABP1, and MLH1) were examined. The CIMP status was determined by the number of methylated promoters as high (⩾5), low (1–4), and negative (0).Results:A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
3
33
1
2
Order By: Relevance
“…We additionally observed that patients with stage IV CIMP positive tumors had a poorer prognosis, irrespective of BRAF and/or MSI status. This has also been observed by others, suggesting that CIMP may be used as a poor prognostic marker for advanced disease.…”
Section: Discussionsupporting
confidence: 79%
“…We additionally observed that patients with stage IV CIMP positive tumors had a poorer prognosis, irrespective of BRAF and/or MSI status. This has also been observed by others, suggesting that CIMP may be used as a poor prognostic marker for advanced disease.…”
Section: Discussionsupporting
confidence: 79%
“…In line with previous studies [4][5][6][7][8], we observed that the TMB-high groups have significantly higher prevalences of MSI status and CIMP phenotype than the TMB-low groups (Fisher's exact test, p<0.01) in the RCC datasets. And tumors with TMB-high exhibited higher BRAF and lower KRAS mutation rate than the TMB-low patients as well.…”
Section: Molecular Differences Between Tmb-high and Tmb-low Samplessupporting
confidence: 92%
“…The different origins consequently contribute to tumors with a different gene expression and mutation profile. RCC patients are reported to be a higher incidence of BRAF, POLE/POLD1 mutation, CIMP, MSI and genome hypermutation [4][5][6][7][8]. Conversely, LCC tumors are characterized by higher frequency of KRAS mutation and chromosomal instability [9].…”
Section: Introductionmentioning
confidence: 99%
“…La vía CIMP se caracteriza por una amplia hipermetilación de los islotes CpG en los promotores de genes supresores de tumores, provocando la inactivación de ellos. Se presenta en 15%-20% de CCR esporádicos y se le asocia a mal pronós-tico 13,14 . Debido a la heterogeneidad y complejidad de los tumores, diversos estudios han propuesto subgrupos moleculares de CCR basados en las 3 vías antes descritas [15][16][17][18][19] .…”
unclassified